Alopecia neoplastica inducing underlying lytic skull metastasis - Rubén Linares Navarro; Héctor Perandones González; Pedro Sánchez Sambucety; Ana De La Hera Magallanes; Manuel Ángel Rodríguez Prieto (Indian Journal of Dermatology, 2022)
Alopecia neoplastica is a rare type of cutaneous metastasis. The most frequent presentation consists of red-violaceous nodular scarring alopecia located at the parietal area. The most frequent primary tumor locations are the breast and gastrointestinal tract. We report a case of alopecia neoplastica that induced an underlying lytic bone metastasis. After a rigorous literature search, we could not find another case showing this mechanism.